Immunophilin FK506 binding protein associated with inositol 1,4,5-trisphosphate receptor modulates calcium flux. - Cameron, A M (1995)
The immunophilin FK506 binding protein 12 (FKBP12) is associated with and modulates the ryanodine receptor calcium release channel of skeletal muscle. Ryanodine receptor has amino acid homology and functional similarity with another intracellular Ca2+ release channel, the inositol 1,4,5-trisphosphate receptor (IP3R). In the present study we show that highly purified preparations of IP3R contain FKBP12. The complex of these two proteins is disrupted by the immunosuppressants FK506 and rapamycin, both of which are known to bind FKBP12 with high affinity. Disrupting the IP3R-FKBP12 interaction increases Ca2+ flux through IP3R, an effect that is reversed by added FKBP12. FKBP12 appears to be physiologically linked to IP3R, regulating its Ca2+ conductance.